A comparative analysis of macro stress-testing methodologies with application to Finland - Sorge, Marco; Virolainen, Kimmo (Journal of Financial Stability, 2006)
This paper reviews the state-of-the-art of macro stress-testing methodologies. We assess the progress made both in the econometric analysis of balance sheet indicators and in the simulation of value-at-risk measures to assess system-wide vulnerabilities. To illustrate the main analytical approaches in the literature, we estimate two different models for stress-testing purposes using data for Finland over the time period from 1986 to 2003. The Finnish experience in the early 1990s appears particularly suited for macro stress-testing as it includes a severe recession with significantly higher-than-average default rates and banks’ loan losses. We highlight a number of methodological challenges that still remain concerning in particular the correlation of market and credit risks over time and across institutions, the limited time horizon generally used for macro stress-testing and the potential instability of reduced-form parameter estimates because of feedback effects.